O metodzie socjologicznej w badaniu prawa - Jedlecka, Wioletta (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The development of different research perspectives has led to the creation of the concept of multifaceted nature of the research on law. Studying the law from different research perspectives, for example a sociological perspective, fosters the so-called external integration of jurisprudence. Sociological methods and techniques cannot, nevertheless, replace the ones lawyers need to apply.
Keywords: wielopłaszyznowość w badaniu prawa; metoda (płaszczyzna) socjologiczna w badaniu prawa; zewnętrzna integracja prawoznawstwa